Purificação, caracterização e aplicabilidade biotecnológica da lectina da alga marinha vermelha Gracilaria ornata (Schneter) - Leite, Yáskara F. M. Marques (2003)
The lectin obtained from the marine alga Gracilaria ornata was purified and characterized by extraction of solube proteins (crude extract) in 25 rnM Tris-HCl buffer, pH 7.5. Among the analysed erythrocytes (human of ABO system, rabbitt and chicken) it was shown that the lectin preferential1y agglutinated rabbitt treated with tripsin enzyme. The haemagglutinating activity reveled that the lectin wasn't dependent on divalent cation Ca2+ and Mn2+ and was shown to be inhibited by the glycoprotein porcine stomach mucin, asialofetuin, apotransferin, porcine and bovine tiroglobulin. The purification procedure was realized by precipitation of the crude extract with 70% saturation ammoniun sulfate (F0/70) followed by ion-exchange chromatography on DEAE-Celulose and affinity chromatography on Mucin-4B-Sepharose. The carbohydrate content of 2.97% of glucose carbohydrat suggest that the lectin under study is a glycoprotein. It was shown an apparent molecular mass of 17.36 KDa by gel filtration on Sephadez G-100 colunn. Eletrophoresis procedures observed under denaturant conditions (SDS-P AGE) with ~-mercaptoetanol, the lectin exhibited a single proteic bando The isoeletric focusing reveled the presence of a sim ple acidic protein band with pl of 5.4. The analysis of the amino acid composition of the purified lectin showed a predominance of amino acids Asx, Glx, Ser, Glu, Ala e Cys, being the high percent obtained to amino acid cistein, a non usual characteristic to lectins of sea algae an superior plants. The hystopatologic evaluation of mices tissues after application of the lectin for via iv., revelead microscopic alterations in the intestine, liver, heart and stomach. The analysis of the insecticide activity of the proteic fractions (crude extract, F0/70 and PII-DEAE), it showed that the energency of the larvas of C. maculatus was inhibed by all the appraised fractions. Meantime, the fractions EB(2.5%) and F0/70(15) inhibited the larval survival considerably.